IMPLEMENTATION OF POST REHABILITATION GUIDANCE TO CLIENTS OF CORRECTIONAL INSTITUTION IN THE FRAMEWORK OF PREVENTION OF RELAPSING TO NARCOTICS CRIMINAL ACTS - djauhari djauhari; Aditya Sarjana Putra (UNISSULA, 2017)
The increased of criminal narcotics is along with economic growth in Indonesia. Narcotics criminal mode includes black drug trafficking, illegal narcotics transactions and misuse. The impact of drug consumption pervades 78% of deaths between the ages of 19-21 years. Government policy is set to overcome the danger of narcotics through the guidance of correctional clients aiming, restoring the client to become a whole and productive people in the life of society. This research used empirical juridical approach through purposive sampling data collection method by interviewing the free competent guided respondents to answer the researcher’s question on the topic of prevention system of Narcotics crime in Penitentiary. The results obtained from this study indicate that the prevention system of narcotic drug crime contains four stages of therapeutic intervention for prison clients namely initial registration, rehabilitation, post-rehabilitation and termination. System output is correctional clients recover from narcotics dependence. The implementation of post-rehabilitation mentoring prioritizes the governance in procedural aspects of administration, fulfillment of facilities, planning, organizing, implementing, monitoring and evaluating. Constraints implementation of post-rehabilitation mentoring includes 2 factors, namely internal and external factors of penitentiary clients. The prevention system improvement solution is the strengthening of client portfolio data upon reassessment in Penitentiary. In addition, budget politics are required in the inflation-friendly provision.